Gadolinium-based layered double hydroxide and graphene oxide nano-carriers for magnetic resonance imaging and drug delivery - Usman, Muhammad Sani; Hussein, Mohd Zobir; Fakurazi, Sharida; Ahmad Saad, Fathinul Fikri (Chemistry Central, 2017)
Gadolinium (Gd)-based contrasts remain one of the most accepted contrast agents for magnetic resonance imaging, which is among the world most recognized noninvasive techniques employed in clinical diagnosis of patients. At ionic state, Gd is considered toxic but less toxic in chelate form. A variety of nano-carriers, including gadolinium oxide (Gd2O3) nanoparticles have been used by researchers to improve the T1 and T2 contrasts of MR images. Even more recently, a few researchers have tried to incorporate contrast agents simultaneously with therapeutic agents using single nano-carrier for theranostic applications. The benefit of this concept is to deliver the drugs, such as anticancer drugs and at the same time to observe what happens to the cancerous cells. The delivery of both agents occurs concurrently. In addition, the toxicity of the anticancer drugs as well as the contrast agents will be significantly reduced due to the presence of the nano-carriers. The use of graphene oxide (GO) and layered double hydroxides (LDH) as candidates for this purpose is the subject of current research, due to their low toxicity and biocompatibility, which have the capacity to be used in theranostic researches. We review here, some of the key features of LDH and GO for simultaneous drugs and diagnostic agents delivery systems for use in theranostics applications.